2021
DOI: 10.1016/j.onehlt.2021.100320
|View full text |Cite
|
Sign up to set email alerts
|

A One-Health evaluation of the burden of cystic echinococcosis and its prevention costs: Case study from a hypo-endemic area in Italy

Abstract: An integrated model, based on a One Health approach, was implemented to estimate the epidemiological and economic outcomes of cystic echinococcosis (CE) in Veneto region, an hypo-endemic area of Northern Italy, and the costs for its prevention. Data and information needed to populate the model were retrieved from published literature, official statistics, expert opinions, or actively searched through data mining (i.e., Hospital and slaughterhouse data), when fundamental data were not available. Human-health an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Over the past three decades, the global burden of CE has almost been halved, possibly attributed to the advancements and widespread adoption of medical techniques like ultrasound diagnosis and rapid immune testing reagents [ 24 ]. Previous studies have found a high prevalence of CE in regions where traditional sheep herding continues to be a major source of income, such as Central Asia, as well as North Africa and the Middle East [ 14 , 24 ]. We also found that approximately half of the global new cases were concentrated in Central Asia, while one-fifth were reported in North Africa and the Middle East.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past three decades, the global burden of CE has almost been halved, possibly attributed to the advancements and widespread adoption of medical techniques like ultrasound diagnosis and rapid immune testing reagents [ 24 ]. Previous studies have found a high prevalence of CE in regions where traditional sheep herding continues to be a major source of income, such as Central Asia, as well as North Africa and the Middle East [ 14 , 24 ]. We also found that approximately half of the global new cases were concentrated in Central Asia, while one-fifth were reported in North Africa and the Middle East.…”
Section: Discussionmentioning
confidence: 99%
“…However, regions with lower SDI indices still had relatively high YLLs. Moving forward, it is crucial that decision-makers prioritise regions with lower SDI indices and implement additional preventive measures and control strategies, while also noting that the CE incidence in areas with high SDI levels showed an increasing trend, which may be attributed to the increased logistics trade and unbalanced development [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pilot study conducted in Argentina [ 94 ] has highlighted the significant advantages of the vaccine in mitigating the transmission of disease among sheep, a promising advancement in the efforts to prevent echinococcosis. These interventions are part of the One Health approach [ 2 , 81 , 96 , 97 ], emphasizing the interconnectedness of human and animal health.…”
Section: Discussionmentioning
confidence: 99%